DerIvaTario: An annotated lexicon of Italian derivatives. (April 2016) - Talamo, Luigi; Celata, Chiara; Bertinetto, Pier Marco
Abstract : We propose an annotation schema for derivational morphology featuring morphological, morphotactic and morphosemantic information concerning the base of the derivative as well as each derivational cycle. This schema was employed in the manual annotation of about 11, 000 Italian derivatives, extracted from the Co LFIS corpus. The outcome is Der Iva Tario, an annotated lexicon of Italian derivatives. The inter-annotator agreement was assessed over several variables of the annotation schema. Der Iva Tario is available as an interactive database to be used for theoretical morphology and psycholinguistic research, and as a resource for automatic tagging of large Italian corpora.